DEVELOPING ECOTOURISM IN YUNNAN: THE KEY ROLE OF EDUCATION IN ACHIEVING LONG TERM SUSTAINABILITY - PRIDEAUX, BRUCE; TAO, YING (ASEAN Journal on Hospitality and Tourism, 2005)
Possessing a unique range of high value ecosystems, landscapes, heritage and indigenous cultures, Yunnan (China) has embraced ecotourism as the major form of tourism activity promoted by the provincial authorities. Unfortunately, few government officials or private sector investors are aware of the requirements for establishing and maintaining a long term sustainable industry based on the principles of ecotourism and sustainabiity. Many of the tourism projects labelled as ‘eco’ have all the hallmarks of mass tourism development. This paper argues that one effective measure to overcome this problem of understanding is through education and suggests a Tourism Education Framework based on the major stakeholder groups who are involved either directly or indirectly in the provinces’ ecotourism industry.